Taming hazardous chemistry by continuous flow technology - Movsisyan, M; Delbeke, E I P; Berton, J K E T; Battilocchio, C; Ley, S V; Stevens, C V (Chemical Society reviews, 2016)
Over the last two decades, flow technologies have become increasingly popular in the field of organic chemistry, offering solutions for engineering and/or chemical problems. Flow reactors enhance the mass and heat transfer, resulting in rapid reaction mixing, and enable a precise control over the reaction parameters, increasing the overall process selectivity, efficiency and safety. These features allow chemists to tackle unexploited challenges in their work, with the ultimate objective making chemistry more accessible for laboratory and industrial applications, avoiding the need to store and handle toxic, reactive and explosive reagents. This review covers some of the latest and most relevant developments in the field of continuous flow chemistry with the focus on hazardous reactions.